Liquid crystalline polymers : proceedings of the International Workshop on Liquid Crystalline Polymers, WLCP 93, Capri, Italy, June 1-4, 1993 - Carfagna, C. (Pergamon, 1994)
The International Workshop on Liquid Crystalline Polymers (LCPs) held in June 1993 in Italy attracted many of the leading researchers in this area of polymer science. The meeting provided a forum for the exchange of research and ideas on current developments and future research and applications of liquid crystalline polymers. This volume consists of a selection of the best papers presented at the meeting covering synthesis and characterization, liquid crystalline thermosets, rheology, blends and composites containing LCPs and transport properties.